2009
DOI: 10.1002/anie.200904333
|View full text |Cite
|
Sign up to set email alerts
|

Isothiourea‐Catalyzed Enantioselective Carboxy Group Transfer

Abstract: The rational design and mechanistic understanding of catalytic systems capable of generating quaternary stereocenters in an asymmetric fashion is a recognized challenge in synthesis.[1] A number of asymmetric Lewis base mediated processes have been developed within this area, [2] in which enantiomerically pure derivatives of 4-(pyrrolidino)pyridine (PPY) and 4-dimethylaminopyridine (DMAP) are elegantly employed by the Fu, [3] Vedejs, [4] and Richards groups, [5] as asymmetric catalysts for the rearrangement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(68 citation statements)
references
References 39 publications
2
65
0
Order By: Relevance
“…Using caesium carbonate, carbamoyl sulfones were converted into the corresponding N -Boc-protected imines 2 that were immediately submitted to List's organocatalytic Mannich reaction [2930]. The resulting aldehydes 3 were not isolated (also in view of their known stereochemical lability) but directly reduced to alcohols 4 [3233]. Purification was carried out through chromatography and, in some cases, by additional crystallization, affording these key intermediates in high ee and de ( syn relative configuration, see Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 99%
“…Using caesium carbonate, carbamoyl sulfones were converted into the corresponding N -Boc-protected imines 2 that were immediately submitted to List's organocatalytic Mannich reaction [2930]. The resulting aldehydes 3 were not isolated (also in view of their known stereochemical lability) but directly reduced to alcohols 4 [3233]. Purification was carried out through chromatography and, in some cases, by additional crystallization, affording these key intermediates in high ee and de ( syn relative configuration, see Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 99%
“…[2] Despite many recent advances, novel methods for the synthesis of highly functionalized pyridines in a selective and high yielding manner from accessible starting materials remains an important goal within the synthetic community. [3] Following the demonstration by Romo and co-workers of generating ammonium enolates [4] from carboxylic acids, [5] we have shown that isothioureas [6,7] catalyze the intermolecular Michael addition/lactonization/lactamization of arylacetic acids and electron-deficient Michael acceptors. [8] To expand this mode of activation, we questioned whether this methodology could be used to access functionalized pyridines.…”
mentioning
confidence: 91%
“…[20] Building upon these precedents, and as part of our existing research programme focusing upon Lewis base catalysis, [21] we have shown that isothioureas such as HBTM 11 and 13 promote the asymmetric O-to C-carboxyl rearrangement of oxazolyl carbonates with high enantioselectivity (up to 94 % ee). [22,23] Notably, recent work by Okamoto has probed the ability of a C(4)-stereodirecting unit within tetrahydropyrimidine-derived isothioureas to promote the asymmetric Steglich rearrangement, [24] whereas Grçger and Dietz have utilised isothioureas for related asymmetric O-to Cacetyl transfer processes. [25] To understand the origins of asymmetric induction in the O-to C-carboxyl transfer process using HBTM 11 we have previously carried out molecular modelling calculations, allowing a simple model for asymmetric induction in this process to be developed ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…C(2)-phenyl substitution (isothiourea 11) leads to optimal reactivity in this series, allowing the reaction temperature to be lowered to À50 8C to achieve optimal product ee values (91 % ee, Further investigations probed the effect of 2,3-disubstitution within the isothiourea catalyst structure (Table 1, entries 18-34). In comparison to HBTM 11, the incorporation of an additional syn-configured C(3)-iPr substituent (isothiourea 13) leads to marginally increased stereoselectivities under optimised conditions (Table 1, entries [18][19][20][21][22], with the incorporation of an electronegative Cl atom within the benzothiazole unit (isothiourea 18) giving negligible change in stereoselectivity ( Table 1, entry 23). The inclusion of alternative C(2)-2-naphthyl or C(3)-methyl units (within 19 and HBTM 2 12 respectively) gave slightly lower enantioselectivities than 13 ( Table 1, entries [24][25][26][27][28].…”
mentioning
confidence: 99%